Предмет: Алгебра,
автор: алина5619
2x+6/x2+x - x-3/(x^2+3x+2)=0 решить уравнение. быстро пожалуйста
Приложения:
![](https://files.topotvet.com/i/a4c/a4c88d1b8936f03bf00664b4ab0adf4b.jpg)
Ответы
Автор ответа:
0
(2x+6)/(x2+x) - (x-3)/(x^2+3x+2)=0
ОДЗ х не равен 0, -1, -2;
(2x+6)/(х(x+1))- (x-3)/((х+2)(х+1))=0
=0
(2x+6)(x+2)-x(x-3)=0
2x^2+4x+6x+12-x^2+3x=0
x^2+13x+12=0
x= -12 x=-1
-1 не проходит по одз
Ответ :-12
ОДЗ х не равен 0, -1, -2;
(2x+6)/(х(x+1))- (x-3)/((х+2)(х+1))=0
(2x+6)(x+2)-x(x-3)=0
2x^2+4x+6x+12-x^2+3x=0
x^2+13x+12=0
x= -12 x=-1
-1 не проходит по одз
Ответ :-12
Похожие вопросы
Предмет: Русский язык,
автор: nurbolatakbota01
Предмет: Математика,
автор: mirorrso46
Предмет: Другие предметы,
автор: diastemirgali9
Предмет: Математика,
автор: ilino4ka81